Body-mass index, blood pressure and cause-specific mortality in India: Prospective study of 500 000 adults - Gajalakshmi, V; Lacey, B; Kanimozhi, V; Sherliker, P; Peto, R; Lewington, S (Elsevier, 2018)
Background The associations of cause-specific mortality with body-mass index (BMI) have been studied mainly in higher-income countries. We relate BMI and systolic blood pressure (SBP) to mortality in a South Asian population. Methods In 1998-2001, 500,810 men and women (age≥35) in Chennai city were interviewed, measured, then visited biennially from 2015, recording structured narratives of any deaths before 31.3.2015 for physician coding; in 2013-14, 10,161 participants were re-surveyed. After excluding all with missing data or chronic disease at recruitment or who died within 2 years (leaving 414,746 participants), Cox regressions (standardised for tobacco, alcohol and social factors) relate mortality rate ratios at ages 35-69 (RRs) to SBP, BMI, or BMI given usual SBP. Findings Mean SBP and BMI at recruitment were 127 mmHg (SD15) and 23 kg/m2 (SD4): correlations with re-survey measurements 14 years later were, respectively, 50% and 88%. Low BMI was strongly associated with poverty, tobacco, and alcohol. Of 29,519 deaths at ages 35-69, half were vascular (mainly cardiac). Cardiac and stroke mortality increased steeply with SBP: as in Western populations, 20 mmHg higher usual SBP approximately doubled vascular mortality, as did diabetes. But, although BMI strongly affected SBP (~1 mmHg/kg/m2) and diabetes prevalence, BMI was little related to cardiac or other vascular mortality, with only small excesses even at BMI≥30 kg/m2. After additionally allowing for the usual SBP, BMI was inversely related to cardiac and stroke mortality throughout 15-30 kg/m2; comparing under vs overweight (15-18.5 vs 25-30 kg/m2), cardiac mortality RR was 1.29 (95%CI 1.20-1.38) and stroke mortality RR was 1.47 (1.23-1.75). Interpretation In this South Asian population, BMI was little associated with vascular mortality, even though BMI increases SBP and SBP increases vascular mortality. Hence, there must be importantly adverse effects of some close correlates of below-average BMI, which could be of relevance in all populations.